The effect of ethanol and alcoholic beverages on gastric emptying of solid meals in humans - Franke, Andreas; Nakchbandi, Inaam; Schneider, Alexander; Harder, Hermann; Singer, Manfred V. (Alcohol and alcoholism, 2005)
Aims: The systematic study of the effect of pure ethanol, alcoholic beverages, and their non-alcoholic components on gastric emptying of solid meals in humans. Methods: 16 fasting healthy male subjects received once weekly 300 ml of the following solutions in random order: 4 and 10% (v/v) ethanol, beer, red wine, 5.5 and 11.4% (w/v) glucose, and water. The test solutions were given either together with a low caloric (270 kcal, n = 8) or a high caloric (740 kcal, n = 8) solid meal. Ultrasonography of the antrum was used to determine gastric emptying. Results: Gastric half emptying time (t(1/2) ) of the high caloric solid meal with water was 131.3 ± 7 min. The ingestion of 4 and 10% (v/v) ethanol (158.8 ± 9.3 and 165.6 ± 6.2 min, respectively), beer (163.1 ± 11 min), and red wine (186.3 ± 8.4 min) resulted in a significantly longer t(1/2) than water. The lag phases after 4 and 10% (v/v) ethanol, beer, and red wine were not significantly different from that of water (48.1 ± 6.5 min). Compared with water, the ingestion of 5.5 and 11.4% (w/v) glucose resulted in a significantly longer t(1/2) (153.8 ± 5 and 168.1 ± 14.4 min, respectively) by increasing the duration of the lag phase. The high caloric meals resulted in a 2-fold prolongation of t(1/2) when compared with the low caloric meals. The effect of the solutions on the gastric emptying times, however, was similar for both test meals. Conclusions: (i) Ethanol in low concentrations of 4 and 10% (v/v) prolongs gastric emptying of solid meals; this inhibitory effect is not dose-dependent. (ii) Alcoholic beverages (beer and red wine) also result in a prolongation of gastric emptying. The inhibitory effect of red wine, but not of beer, is more pronounced than that of the corresponding ethanol concentration and amount. (iii) The inhibitory effect of ethanol and alcoholic beverages is mainly induced by a prolongation of the gastric emptying phase (without affecting the lag phase), whereas 5.5 and 11.4% (w/v) glucose prolong the lag phase in a dose-dependent manner. (iv) The inhibitory effect of ethanol, beer, and red wine on gastric emptying does not depend on the caloric content of the meal.
Gesehen am 13.05.2022